Comparison of Two Fixation Methods for Arthrodesis of the Calcaneocuboid Joint: A Biomechanical Study. (January 2015) - Milshteyn, Michael A.; Dwyer, Mark; Andrecovich, Christopher; Bir, Cynthia; Needleman, Richard L.
Background: The traditional fixation for a calcaneocuboid (CC) arthrodesis in triple arthrodesis is with a 6.5-mm cancellous screw. This procedure can be technically challenging. Fixation with a locking compression plate (LCP) may be easier to perform while achieving compression perpendicular to the fusion site. The purpose of this study was to compare the load to failure and the stiffness for each fixation method. Methods: Five matched-pair cadaver feet had an arthrodesis of the CC joint. For each matched pair, one was fixed with a screw and the other with an LCP. Surface bead markers were applied. Each specimen was then secured to a material testing machine through the calcaneus. The plantar surface of the cuboid faced the hydraulic ram to simulate weightbearing. A force was applied while the specimen was recorded with a high-resolution camera. The endpoint was maximal force at 2-mm separation between the calcaneus and cuboid measured along a horizontal axis. Results: The average force to failure and the average stiffness in the screw group were significantly less than the LCP group ( P < .05). The screw construct failed in pullout from the cuboid; the LCP construct failed by plastic deformation of the plate. Conclusion: Calcaneocuboid joint fixation with the LCP withstood a higher load until failure and demonstrated greater stiffness than with a 6.5-mm cancellous lag screw. Clinical Relevance: The use of LCP fixation can be considered as an alternative to oblique lag screw fixation for CC arthrodesis in a triple arthrodesis. It remains to be determined if LCP fixation leads to better clinical outcomes.